Possible Protecting Role of TNF-α in Kainic Acid-induced Neurotoxicity Via Down-Regulation of NFκB Signaling Pathway - Zhang, Xing-Mei; Zheng, Xiang-Yu; S. Sharkawi, S.; Ruan, Yang; Amir, Naheed; Azimullah, Sheikh; Y. Hasan, M.; Zhu, Jie; Adem, Abdu (Current Alzheimer Research, 2013)
We have shown previously, that mice lacking tumor necrosis factor-α (TNF-α) receptor 1 (TNFR1) exhibit greater hippocampal neurodegeneration, suggesting that TNFR1 may be protective in kainic acid (KA)-induced neurotoxicity. Here, we aim to clarify the role of TNF-α in neurodegenerative disorders and to elucidate its potential signaling pathways. TNF-α knockout (KO) mice and wild-type (WT) mice were treated with KA intranasally and, seizure severity measures obtained, Behavioral tests, including Elevated Plus-Maze™, open-field, Y-maze were also performed. Five days following KA treatment, immunohistochemical methods were used to assess neuronal degeneration and glial activation. The production of nitric oxide (NO) and the expression of nuclear factor kappaB (NF-αB) and AKT in the hippocampus were also measured. Compared with WT mice, TNF-α KO mice were more susceptibile to KA-induced neurotoxicity, as demonstrated by more severe seizures, measurable behavior changes, greater neuronal degeneration in hippocampus, elevated glial activation and NO production. Additionally, KA-treatment up-regulated the expression of NFκB in TNF-α KO mice to a greater degree than in KA-treated WT mice. We conclude that TNF-α deficiency adversely influences KAinduced neurotoxicity and that TNF-α may play a protective role in KA-induced neurotoxicity via the down-regulation of NFκB signaling pathway.
Keywords: kainic acid